EVALUATIVE RESPONSES IN MODERN ENGLISH FICTION - Tetiana Myroniuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The process of communication implies information exchange, mutual influence, and evaluation of speakers. An addressee is an important participant of this process, yet little is known about him as a person who receives and evaluates an addresser's utterance. This is particularly significant because the addressee influences the further course of communication by his/her own responses due to the rules of turn taking. An evaluative response is thus an evaluative speech act that serves as the perlocutionary effect of an addresser's utterance and simultaneously expresses some intention concerning an interlocutor. The present paper aims to identify, classify and analyse the types of evaluative responses from a pragmatic perspective. The empirical material consists of 30 modern American and British novels, or 3400 dialogues containing evaluative responses. The theoretical basis of the investigation integrates the main principles of pragmalinguistics and speech act theory. In view of this, we suggested a pragmatic typology of evaluative responses based on an addressee's speech reaction to the received stimulus. The study claims the universality of an evaluative response as a speech act. It may provide not only emotional perception of reality but also contribute to its adequate comprehension and even exert direct or hidden influence on verbal and nonverbal actions of an interlocutor.